Design, Synthesis, and Development of Pyrazolo[1,5-a]pyrimidine Derivatives as a Novel Series of Selective PI3Kδ Inhibitors: Part II-Benzimidazole Derivatives - Mariola Stypik; Stanisław Michałek; Nina Orłowska; Marcin Zagozda; Maciej Dziachan; Martyna Banach; Paweł Turowski; Paweł Gunerka; Daria Zdżalik-Bielecka; Aleksandra Stańczak; Urszula Kędzierska; Krzysztof Mulewski; et al. (MDPI AG, 2022)
Phosphoinositide 3-kinase (PI3K) is the family of lipid kinases participating in vital cellular processes such as cell proliferation, growth, migration, or cytokines production. Due to the high expression of these proteins in many human cells and their involvement in metabolism regulation, normal embryogenesis, or maintaining glucose homeostasis, the inhibition of PI3K (especially the first class which contains four subunits: α, β, γ, δ) is considered to be a promising therapeutic strategy for the treatment of inflammatory and autoimmune diseases such as systemic lupus erythematosus (SLE) or multiple sclerosis. In this work, we synthesized a library of benzimidazole derivatives of pyrazolo[1,5-a]pyrimidine representing a collection of new, potent, active, and selective inhibitors of PI3Kδ, displaying IC50 values ranging from 1.892 to 0.018 μM. Among all compounds obtained, CPL302415 (6) showed the highest activity (IC50 value of 18 nM for PI3Kδ), good selectivity (for PI3Kδ relative to other PI3K isoforms: PI3Kα/δ = 79; PI3Kβ/δ = 1415; PI3Kγ/δ = 939), and promising physicochemical properties. As a lead compound synthesized on a relatively large scale, this structure is considered a potential future candidate for clinical trials in SLE treatment.